2010
DOI: 10.1007/s11010-010-0472-z
|View full text |Cite
|
Sign up to set email alerts
|

l-Carnitine is essential to β-oxidation of quarried fatty acid from mitochondrial membrane by PLA2

Abstract: Mitochondrial beta-oxidation is an important system involved in the energy production of various cells. In this system, the function of L-carnitine is essential for the uptake of fatty acids to mitochondria. However, it is unclear whether or not endogenous respiration, ADP-induced O(2) consumption without substrates, is caused by L-carnitine treatment. In this study, we investigated whether L-carnitine is essential to the beta-oxidation of quarried fatty acids from the mitochondrial membrane by phospholipase A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…It is an essential cofactor in the transfer of fatty acyl groups into the mitochondrial matrix, where they undergo beta-oxidation [6,12]. Carnitine also plays a role in the transfer of acetyl and other short acyl groups from peroxisomes to mitochondria for further oxidation [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is an essential cofactor in the transfer of fatty acyl groups into the mitochondrial matrix, where they undergo beta-oxidation [6,12]. Carnitine also plays a role in the transfer of acetyl and other short acyl groups from peroxisomes to mitochondria for further oxidation [13].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence suggests that carnitine and its derivatives acetyl-L-carnitine and propionyl-L-carnitine enhance glucose utilization by stimulating the activity of pyruvate dehydrogenase complex [9], which is a key enzymatic complex in glucose oxidation, because intramitochondrial acetyl-CoA can be converted with carnitine into acetyl-L-carnitine (ALC) via the carnitine acetyltransferase that is then transported out of the mitochondria [10]. L-Carnitine is an amine key substrate in a family of carnitine acyltransferases, transferred reversibly between active units of acyl carnitine and co-enzyme A to preserve homoeostasis for a wide range of traffic that are crucial for acyl intermediary metabolism and cellular regulation [11].Various analogues of L-carnitine have been synthesized to study their mode of action and the structural features of their binding sites [12,13]. The phosphorus analogues of naturally occurring amino acids, which are produced by certain organisms, are of great interest in bioorganic and medicinal chemistry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…L-carnitine increases the rate of fatty acid transport to the mitochondria and, in fact, has been shown to be essential to b-oxidation of quarried fatty acids from the mitochondrial membrane. (26,27) It has been shown that administration of exendin-4 leads to the reduction of oxidative stress in steatotic models. (23) It protects the hepatocytes from ischemic injury by inhibiting cell death and stimulation of lipolysis.…”
Section: Reduction Of Iri and Steatosis With Nelpmentioning
confidence: 99%
“…Carnitine is essential for the β-oxidation of fatty acids in mitochondria to generate adenosine triphosphate (ATP) in living cells (12,13). Under normal conditions, 70-80% of human carnitine is obtained through dietary means, although the liver, kidney and brain are capable of biosynthesizing carnitine from lysine and methionine.…”
Section: Introductionmentioning
confidence: 99%